Penggunaan Problem Based Learning Dengan Bantuan Algoritma Dalam Menyelesaikan Soal Konsep Mol Bagi Siswa SMA Negeri 2 Tondano - Gumuru, Eliezer; Lumingkewas, Sonny; Waworuntu, Freetje (General Chemistry Journal, 2025)
The aim of this research is to find out whether there is an increase in learning outcomes before and after using Problem Based Learning model with the help of an algorithm in solving Mole Concept questions for students at SMA Negeri 2 Tondano. This research was conducted in class XI of SMA Negeri 2 Tondano in the 2023/2024 academic year with a total of 22 students. This research uses a quantitative method with a one group pretest posttest design. Data collection techniques performed using learning outcomes test where given pretest was given treatment and posttest after treatment in the form of model based basible learning with the help of algorithm. Based on the results of the hypothesis test using paired sample t-test tested ac2 = 21,81> ttable = 1.71, then H0 was rejected and H1 was accepted. Therefore it can be concluded that there are enhancement in learning outcomes before and after using Based Learning Problems with the help of algorithms in solving the problem of mole Concept for SMA Negeri 2 Tondano students